EFFECTS OF CARBOFURAN ON THE REPRODUCTIVE CAPACITY OF A FRESHWATER SNAIL, RADIX QUADRASI, UNDER LABORATORY CONDITIONS - CARING, VIRGINIA S (BIOTROPIA, 2011)
The effects of 4 sublethal concentrations of carbofuran (250, 500, 1000 and 2000 ppm) on the reproductive capacity of R. quadrasi was determined. Results showed that incubation period is delayed and inhibited by 1000 and 2000 ppm carbofuran but not by lower concentrations. The hatching period is longer in treated snails and not all eggs hatch in the 1000 and 2000 ppm treatment. The percentage of hatching is inversely proportional to the carbofuran concentration. Oviposition was delayed in all the treated stages and at all dosages. The higher the carbofuran concentration, the later the onset of oviposition. The reproductive period is shortened. Fecundity was decreased in snails treated at EMB and SM. However, only the 2000 ppm carbofuran concentration showed an adverse effect on the snails exposure at PSM.